AUTOBIOGRAPHICAL LECTURES OF LEADERS IN ART EDUCATION, 2001-2021 a selection of self-reflections and living histories - Baer, Stephanie A. ([S.l.] : ROUTLEDGE, 2024)
This scholarly collection is a continuation of a lecture series highlighting the essential nature of biography in the history of art education. The editors feature 16 prominent art educators, organized into one of three chronological sections spanning the past two decades. The contributing art educators explore influences that shaped their beliefs about art education and the arts, describe their career paths, explain their philosophy of art education and its development, and advise, predict, or speculate about the future. Every chapter concludes with essential questions and instructional resources to guide readers in their reflection. In reading these lectures, art education faculty, students, and any adjacent professional to the arts and art history can learn the importance of biographical and autobiographical study to research. Beyond research, readers can use the lectures to consider and question teaching and mentoring relationships, the power of influence, and what qualities may contribute to the recognition of exemplary success for art educators.
Keywords: Art teachers -- Biography; Art -- Study and teaching; EDUCATION / General; EDUCATION / History